Coexistence and commerce : guidelines for transactions between East and West - Pisar, Samuel (UK : Allen Lane: The penguin press, 1970)
In this book, the readers will find the complex ideological, political, strategic, economic and commercial factors at work between free enterprise and state enterprise.
includes notes
includes index
ijb, 16/01/2019
Loans
Keywords: Communist countries; East-West trade; Commercial law